Implementation Of Content Based Image Retrieval For Search Engine - yuliawati, Dona; -, Nisar; Rahardi, Agus; Irianto, Suhendro Yusuf; Karim, Arman Suryadi (Prosiding International conference on Information Technology and Business (ICITB), 2018)
Searchengine is defined as web page or website that collects and organizes all content on the internet, here the user input a question or query, then the search engine will provide links to content that reflects what he wants. Until now, there are two problems paid attention by the experts in relation with search engines namely images in a database and the internet using text or keyword. These problems are far away from the expected. The search image by using the text or keyword is very biased and difficult to justify because the keyword is very difficult to explain the information in an image. Content base image Retrieval is method return the image or image retrieval with the use of content the content contained in the picture or image, i.e. elements that can be taken from within the image that can be converted into a value such as color, shape, texture, line and other elements. Elements that are changed are contained in the image are converted in the form of value is to calculate each element and save the value into a histogram which will be used in the comparison process image and the process returns the image or image retrieval.Keywords: Search engine, content base image retrieval, flora, fauna